PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MUTIARA AGUNG - Irawan Noor (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this study was to determine how the influence of competence and motivation to employee performance PT. Mutiara Agung. The research method was used by Explanatory Analysis approach that explains the causalistic relationship between variables. Sampling technique was using Slovin formula which further in sampling with simple random sampling method. This can be done because the characteristics of respondents in this research was homogeneous, that is the employees of PT. Mutiara Agung. Based on the results of this research, there is a significant influence between competence and motivation variables to employee performance PT. Mutiara Agung, with using F test, where F count is bigger than F table (38,365> 3,214). Conclusion: There is significant influence which is explained by result from R square is 0,641 which mean that competence and motivation variable give contribution equal to 64,1% to employee performance variable, while the rest equal to 35,9% was donated by other variable which not examined. Suggestions that the authors convey to the company is the competence contained in the company should still be improved and the leader provides motivation to employees such as with rewards on employees' achievment.